METASTABLE BEHAVIOR OF DEEP LEVELS IN HYDROGENATED GAAS - CHO, HY; KIM, EK; MIN, SK; CHANG, KJ; LEE, C (AMER INST PHYSICS, 1991)
New metastable behavior of deep levels is found in hydrogenated GaAs doped with Si. A deep level at 0.60 eV below the conduction-band minimum (E(c)) is generated during hydrogenation and shows metastable for the E(c) - 0.42 eV trap. From the defect transformations observed in biased anneals, these defects are found to be metastable defects associated with hydrogen atoms. Especially, the 400 K biased-anneal experiments indicate that an E(c) - 0.33 eV trap could be an electric field induced defect, transformed from other intrinsic defects. The E(c) - 0.60 eV trap in hydrogenated GaAs could be a hydrogen complex associated with E(c) - 0.42 eV trap and the hydrogen atom plays an important role in a metastability of deep level defects in GaAs.
Keywords: DONOR NEUTRALIZATION; ATOMIC-HYDROGEN; ELECTRON TRAP; DEFECT; PASSIVATION; INP; SEMICONDUCTORS; SILICON; IDENTIFICATION; EL2